1987
DOI: 10.1190/1.1442332
|View full text |Cite
|
Sign up to set email alerts
|

The dielectric constant of sandstones, 60 kHz to 4 MHz

Abstract: Complex impedance data were collected for eight sandstones at various levels of water saturation [Formula: see text] in the frequency range of 5 Hz to 4 MHz. The measurements were made using a two‐electrode technique with platinum electrodes sputtered onto the flat faces of disk‐ shaped samples. Presentation of the data in the complex impedance plane shows clear separation of the response due to polarization at the sample‐electrode interface from the bulk sample response. Electrode polarization effects were li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
147
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(153 citation statements)
references
References 28 publications
5
147
1
Order By: Relevance
“…The plots for the rocks in this study are shown in Figure 1 (for dry rock samples) and Figure 2 (for partially saturated rock samples). Knight 11 as well as Knight and Nur 13 have established the existence of a critical frequency f 0 that separates the low frequency electrode polarization effects from high frequency bulk material polarization region of r   for Berea sandstones. In the present study, only few samples depict this critical frequency.…”
Section: Cole-cole Plotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plots for the rocks in this study are shown in Figure 1 (for dry rock samples) and Figure 2 (for partially saturated rock samples). Knight 11 as well as Knight and Nur 13 have established the existence of a critical frequency f 0 that separates the low frequency electrode polarization effects from high frequency bulk material polarization region of r   for Berea sandstones. In the present study, only few samples depict this critical frequency.…”
Section: Cole-cole Plotsmentioning
confidence: 99%
“…The efficient use of these tools depends on the understanding of the mechanisms of dielectric behaviour of rocks [11][12][13][14][15][16][17][18][19] . Broadband frequency dielectric measurement of heterogeneous media is based on the strong relationship between the fluid content and dielectric permittivity.…”
mentioning
confidence: 99%
“…However, due to the extraordinarily complex heterogeneity of porous rocks, there are still many disputes over the conductive and dielectric mechanisms in rocks (Clavier et al 1984;Zemanek 1989;Hamada and Al-Awad 1998). Scholars have proposed many conductive models for rocks, of which the most representative is the dual-water argillaceous sandstone conductive model proposed by Waxman andSmits in 1968 (Waxman andSmits 1968;Knight and Nur 1987;Hassoun et al 1997). …”
Section: Introductionmentioning
confidence: 99%
“…Each type of polarization will vanish past a certain frequency, which is determined by the inertial moment of the particles in question, frictions and electrostatic forces. They expressed that the electronic polarization, corresponding to rock permittivity, occurs at a range of 1Hz to approximately 1×10 8 Hz; molecular orientation, corresponding to the water molecular permittivity, occurs at range of 1Hz to approximately 1×10 10 Hz; and interfacial polarization, corresponding to pore geometry and ions, occurs at a range of 1Hz to approximately 1×10 16 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies proved that most rocks and minerals show dielectric dispersion in the low-frequency region from a few Hz to several MHz. [15][16][17] At low frequencies, the dielectric dispersion of geological materials is believed to be caused by the polarization associated with charge buildup at the grain boundaries or grain imperfections. However, grain sizes and their distribution also control the frequency-dependent ε' values of the geological samples.…”
Section: Introductionmentioning
confidence: 99%